PENERAPAN KURIKULUM MERDEKA DALAM PEMBELAJARAN ANAK BERKEBUTUHAN KHUSUS DI SLB WIYATA DHARMA 4 GODEAN - Aulia Az Zahra; Naa’il Eka Mukhbita; Ulla Khoirotun Nisaq; Karen Tri Murti; Ainur Yandi; Muhammad Asril Sermaf; An-Nisa Apriani (Jurnal Pendidikan Nusantara, 2026)
This study aims to describe the implementation of the Merdeka Curriculum in learning for Children with Special Needs at SLB Wiyata Dharma 4 Godean. This research employed a descriptive qualitative approach, with data collected through interviews with Special Education teachers. The Merdeka Curriculum is implemented adaptively by adjusting school conditions and students’ characteristics while still referring to the established learning outcomes. Learning activities are designed through lesson plans and teaching modules developed based on the results of students’ initial assessments. The learning system applies study groups that are organized according to students’ abilities rather than grade levels. The dominant learning methods used are direct instruction and hands-on practice utilizing concrete learning media. Assessment is conducted through formative and summative assessments tailored to the abilities and needs of students with special needs. The results indicate that the implementation of the Merdeka Curriculum supports effective learning for students with special needs, although challenges related to students’ unstable emotional conditions remain.